The effective parental responsibility to guarantee the exercise of the rights of children and adolescents in family conflicts - Jiménez Erazo, Karla Pamela (2021)
In order to guarantee the effective enjoyment of the rights of children and adolescents, it is essential that the persons responsible for their care respect, demand, and enforce such rights, leaving aside their interests. In the past, the care and protection of minors have been exercised through the power of the father of the family, an almost absolute or unlimited power over his children and his property. Currently, although it is not applied literally, it is poorly implemented when the wishes or whims of the person exercising it are put first, especially in family matters, which makes it impossible for children and adolescents to fully exercise their rights, including their right of access to justice since they require an adult to assert them in their name and on their behalf. Thus, as time went by, the children not recognized by their parents did not receive food or have access to social security and, unfortunately, they were denied the right to know their origin, their identity and to live with his parent. This forces them to turn to the courts when they become of legal age to request access to justice, since when they were minors they did not have it and, therefore, were unable to assert their rights due to a deficient exercise of parental authority.